Does VALIDATE-SWEDEHEART invalidate the use of bivalirudin in myocardial infarction? - Ong, Caroline; Bangalore, Sripal (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Over the past two decades, technological advances in percutaneous coronary intervention (PCI) [such as 2nd generation drug eluting stents (DES), use of transradial access] and antithrombotic therapy (more potent P2Y12 agents) have made PCI safer and more effective in treating patients with acute coronary syndrome (ACS). The use of direct and indirect thrombin inhibitors along with glycoprotein IIb/IIIa inhibitors (GPI) during PCI have contributed to improved angiographic and clinical outcomes, but at the cost of increased bleeding complications and its attendant risks of morbidity and death (1).